Replenish the Earth and Subdue it - Aladeko, J.B. (Obafemi Awolowo University Press, 2013)
The lecture shows that energy and materials constitute an inseparable entity. While we need materials to replenish our country, we need energy to subdue it and generate new materials. Results of various surveys and scientific investigations have confirmed that Nigeria is blessed with a rich store of materials and energy resources the types that if optimally used can transform it into one of the greatest countries on earth. Mention any element or energy resource and you would find that Nigeria has it. However, if the question is asked as to how these resources have been utilized so far, the answer is likely to be that we have not done what we should but we have wasted those resources we should not and there is no "economic health" in us. For the past decade or so, Nigeria has leaned heavily on a single resource - Petroleum which yields at least 80% of its foreign earnings. It is even doubtful if Nigeria derives full benefits from the oil as most of the sensitive technological aspects of the industry are effectively controlled by foreigners. Nigeria also burns off its rich store of natural gas. All these must stop if we are to survive the present and live to the future. We must develop other resources and re-cycle our materials for best results.